Epidemiology of myotonic dystrophy type 1 in the population of central Serbia - Mladenović Jelena (Vojnosanitetski Pregled, 2005)
The objective of this epidemiological survey was to estimate the frequency and distribution of Myotonic dystrophy type 1 (MD1) (Steinert's disease) in central Serbia, during the period 1983-2002. The data on the number of diagnosed MD1 patients were obtained using the analysis of hospital records, which were examined in all the relevant neurological institutions in central Serbia in the mentioned period. Incidence rate and prevalence were used for the data analysis. In the study period in central Serbia, 154 patients (78 males and 76 females) with MD1 were identified. The average annual incidence rate of MD1 was 1.3 (95% CI-confidence interval 0.1-7.2) per 1,000,000 population, 1.4/1,000,000 (95% CI 0.1-7.2) for males, 1.3/1,000,000 (95% CI 0.1-7.2) for females. The trend of MD1 incidence rates in the observed period in central Serbia had a tendency of the statistically significant decrease, according to the linear model, in both male (y=0.205-0.0066x, p=0.021) and female populations (y = 0.1788-0.0048×, p = 0.032). The prevalence of MD1 on December 31, 2002 in central Serbia was 3.8/100,000 (95% IP 3.2-4.6), 3.7/100,000 (95% IP 3.3-4.8) for males, 3.3/100,000 (95% IP 3.0-4.4) for females.